Associations of selected aspects of socioeconomic status with overweight and obesity in women with breast cancer and a population-based control group - Quantitative data analysis using data from the MARIE-study baseline - Annika Kreienbrinck (2019)
Introduction: Breast cancer is the most common malignant tumour among women. Each year it affects about 2.1 million women worldwide, and the lifelong risk for development is approximately 12%. Though previous research has documented risk factors which con-tribute to the development of breast cancer, the potential influence of socioeconomic sta-tus and its related factors is only recently getting more attention. As maintaining a healthy weight is one of the recommended main preventive actions, this thesis examined the as-sociations of the selected SES aspects marital status, relationship status, education level and autonomy in occupation level with overweight and obesity, in breast cancer patients and a population-based control group. Methods: The analyses were performed with the baseline data of the MARIE-study, a population-based case-control study, which was assessed between 2002 and 2005 in the regions of Hamburg and Rhein-Neckar-Karlsruhe. The sample comprises of 10,882 fe-male participants, aged between 50-74 years. The statistical analyses included bivariate and in the form of binary logistic regression analysis, multivariate methods. The tests were run using SPSS version 25. Results: The results showed that individuals of the case and control groups with the low-est education level had significantly increased odds of overweight and obesity when com-pared to the highest education level (i.e. OR for breast cancer patients: 3.52, 95% CI 2.87-4.32). The autonomy in occupation level presented similar findings (i.e. OR for obesi-ty in controls: 1.95, 95% CI 1.65-2.30), where it could be observed that the lower the cat-egory, the higher the odds of being overweight and obese. Relationship status and marital status presented inconclusive findings, with partly significant results in the individual cate-gories. Conclusion: A low education level and low autonomy in occupation level were associated with overweight and obesity. Comparison of the BCP and population-based control group’s results showed no striking differences. Partial aspects of the socioeconomic sta-tus, i.e. income, and other behavioural factors, as well as the general health status, were not considered in this work and could offer an approach for further investigations. This thesis may serve as a starting point for future research where, i.e. in the context of SES aspects and overweight/ obesity, the survival of BCP could be focused on.